2002
DOI: 10.2337/diacare.25.8.1439
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hyperglycemia in Nitrotyrosine Postprandial Generation

Abstract: OBJECTIVE -Recently, much attention has been paid to the possibility that postprandial hyperglycemia may be a cardiovascular risk factor in diabetes. Oxidative stress has been involved in the pathogenesis of diabetic complications, and increased plasma levels of nitrotyrosine, a product of peroxynitrite action, have been found in the plasma of diabetic subjects. The aim of the present study was to evaluate whether postprandial hyperglycemia is accompanied by nitrotyrosine generation and, if so, to explore a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
139
2
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(160 citation statements)
references
References 39 publications
15
139
2
4
Order By: Relevance
“…Our results, within the context of the data obtained from Ceriello et al and Scognamiglio et al, indicate a significantly reduced oxidative stress and improved postprandial microvascular blood flow following injection of rapid-acting insulin analogs (such as insulin glulisine) compared with regular human insulin (4,12).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our results, within the context of the data obtained from Ceriello et al and Scognamiglio et al, indicate a significantly reduced oxidative stress and improved postprandial microvascular blood flow following injection of rapid-acting insulin analogs (such as insulin glulisine) compared with regular human insulin (4,12).…”
Section: Discussionsupporting
confidence: 52%
“…There are considerable data indicating that postprandial glucose levels may be an independent risk factor for cardiovascular disease and are more predictive than fasting hyperglycemia (10,11). It has been shown that acute hyperglycemia affects endothelial function and impairs microvascular blood flow (4), which could be attributed to an increase in nitrotyrosine, leading to the generation of superoxide anions and an increase in oxidative stress (12). In addition, hyperglycemia decreases the bioavailability of nitric oxide (NO) and reduces the ability of the vasculature to respond to NO, which leads to vasoconstriction and an increase in atherogenic potency (13).…”
Section: Discussionmentioning
confidence: 99%
“…1), compared with exposure to continuous normal glucose or high glucose. The markers chosen were: (1) the basement membrane protein fibronectin, shown to be overexpressed in the vessels of diabetic patients [23]; (2) the signalling kinase PKC-β, stimulated by high glucose through a cofactor, diacylglycerol [24,25]; (3) the mitochondrial pro-apoptotic protein BCL-2 family member Bax, indicative of mitochondrial stress [26] and associated with vascular diabetic complications [27]; (4) the DNA damage protein PAR, a product of PARP, shown to be a critical factor in the development of vascular diabetic complications [7]; (5) p47phox, an inducible subunit of the enzyme NAD(P)H oxidase, shown to be a source of ROS in the endothelium of diabetic patients [28]; and (6) the protein adduct 3-NY, a marker of oxidative stress and vascular diabetic complications [29][30][31][32]. As has been shown previously, chronic high glucose resulted in significantly increased levels of: fibronectin [10]; phospho-(activated) PKC-α/βII [25]; p47phox [33]; and 3-NY [31], while the increase in Bax was not statistically significant [27] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the possibility that postprandial hyperglycaemia increases oxidative stress and inflammation in healthy subjects has previously been reported [12,13]. Furthermore, evidence showing that modulation of postprandial hyperglycaemia by diet or an insulin analogue in type 2 diabetes [25][26][27], and by pramlintide [28] in type 1 diabetes, is accompanied by a significant decrease of oxidative stress, while nuclear factor kappa B activation is decreased when controlling postprandial hyperglycaemia by acarbose [24], convincingly suggests that the effect of S21403 on postprandial oxidative stress and inflammation is related to its ability to reduce postprandial hyperglycaemia.…”
Section: Discussionmentioning
confidence: 98%